2014
DOI: 10.1007/s15010-014-0703-4
|View full text |Cite
|
Sign up to set email alerts
|

Oseltamivir prophylaxis in controlling influenza outbreak in nursing homes: a comparison between three different approaches

Abstract: Comparison of influenza outbreaks in three NHs revealed that the duration of the outbreak was the shortest in the NH where prophylaxis with oseltamivir was given to all residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The lack of appropriate treatment and preventive strategies for influenza in ACFs leads to a greater burden of illness and results in poorer outcomes. Whereas there is variable evidence to support the use of OP in ACFs [15], this large cohort study adds to the growing body of evidence on the effectiveness of oseltamivir used prophylactically to prevent influenza in ACFs during an outbreak. This study found that when used as prophylaxis, oseltamivir was highly effective in preventing new clinical cases at an individual level in influenza outbreaks in dementia-specific units and high care settings when compared with nondementia-specific wings and low care settings.…”
Section: Discussionmentioning
confidence: 97%
“…The lack of appropriate treatment and preventive strategies for influenza in ACFs leads to a greater burden of illness and results in poorer outcomes. Whereas there is variable evidence to support the use of OP in ACFs [15], this large cohort study adds to the growing body of evidence on the effectiveness of oseltamivir used prophylactically to prevent influenza in ACFs during an outbreak. This study found that when used as prophylaxis, oseltamivir was highly effective in preventing new clinical cases at an individual level in influenza outbreaks in dementia-specific units and high care settings when compared with nondementia-specific wings and low care settings.…”
Section: Discussionmentioning
confidence: 97%
“…Hospitalisations and deaths were non-influenza specific. 21 Findings from a number of observational and descriptive studies generally favour the recommendation of using antiviral IP to control outbreaks of influenza in the LTCF. 22–26 These studies ranged from case series to uncontrolled cohort studies, before-and-after design, outbreak reports and varied in the sample size, degree and scope of analyses undertaken.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined both the clinical and economic benefits of prophylaxis with anti-flu agents ( 21 , 22 ). However, few studies have estimated the efficacy and the cost of prophylaxis of anti-flu agents when an outbreak happens at a single hospital.…”
Section: Discussionmentioning
confidence: 99%
“…The development of resistance when using neuraminidase inhibitors is also unknown. However, the prophylactic usage of oseltamivir is now indicated to manage flu outbreaks for all nursing home residents, as the duration of flu outbreaks was shown to be the shortest in nursing homes where prophylaxis with oseltamivir was given to all residents ( 22 ).…”
Section: Discussionmentioning
confidence: 99%